2009
DOI: 10.1353/hpu.0.0225
|View full text |Cite
|
Sign up to set email alerts
|

Students Who Participate in a Student-Run Free Health Clinic Need Education about Access to Care Issues

Abstract: We surveyed first-year medical students about preparedness for work at student-run clinics, and for addressing patients' access to care, and social issues. Most students did not know how to get uninsured patients ongoing care or medications outside of the student-run clinic. A large majority of students desired an orientation addressing these issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The predominance of volunteers from lower socioeconomic and underrepresented backgrounds warrants further exploration of how many of the volunteers have had limited access to healthcare themselves and how that has impacted their attitude towards healthcare in general and community-oriented medicine in particular. The results appeared to follow the general trends observed in a similar study of 209 medical students who were found to lack knowledge pertaining to patients’ social and access-to-care issues, particularly in underserved and uninsured populations [ 10 ]. Those who participated in SRFCs gained experience over time and became comfortable providing medical assistance and outside access to primary and specialty care to their patients.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The predominance of volunteers from lower socioeconomic and underrepresented backgrounds warrants further exploration of how many of the volunteers have had limited access to healthcare themselves and how that has impacted their attitude towards healthcare in general and community-oriented medicine in particular. The results appeared to follow the general trends observed in a similar study of 209 medical students who were found to lack knowledge pertaining to patients’ social and access-to-care issues, particularly in underserved and uninsured populations [ 10 ]. Those who participated in SRFCs gained experience over time and became comfortable providing medical assistance and outside access to primary and specialty care to their patients.…”
Section: Discussionsupporting
confidence: 73%
“…The elements of the survey were modeled after those in the existing literature on medical students at SRFCs [ 10 ] and volunteers in palliative care hospices [ 6 , 8 , 11 ]. The survey included questions about the volunteers’ general demographics, knowledge of the healthcare process, interaction with staff, and satisfaction with the orientation and the volunteer experience.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 4 provides additional examples of SRFC outcomes. 47 Some established SRFCs have had difficulty evaluating their outcomes, often because the outcomes are not identified during planning or are not specific and measurable. An SRFC in Philadelphia assumed that alumni would become primary care physicians as a result of participation in the SRFC; however, they did not collect specific data to support this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research from medical schools and students across the country has sought to take advantage of each of these role-characteristics to improve care for people who are homeless within institutions. This research focused primarily on improving attitudes and knowledge around houselessness among medical students [ 17 – 22 ]; altering didactic medical education to include training on caring for people who are houseless or otherwise excluded from care [ 20 , 23 – 26 ]; facilitating opportunities to care for people who are houseless in clinical settings [ 25 , 27 – 29 ]; and more broadly improved the social accountability of medical schools and the institutions they are a part of [ 30 33 ]. These efforts are significant not only for enacting change at the institutional level, but also for preparing the next generation of physicians to provide full-spectrum and empathic care to people who are houseless.…”
Section: Introductionmentioning
confidence: 99%